2018
DOI: 10.4236/ojanes.2018.88024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Google Glass™ with Camera Adaptor and GoPro™ as Teaching Tools for Endotracheal Intubation in the Austere Medical Environment

Abstract: Objective: Endotracheal intubation (ETI) is a life-saving emergency procedure, but it is a complex skill that is difficult to teach. Recent studies have shown that video laryngoscopy is effective in teaching ETI to learners at various levels of medical expertise; however, it has proven to be costly and provides images of inconsistent quality. In this educational proof of concept feasibility convenience sample pilot study, we aim to explore and compare the effectiveness of using modified Google Glass™ (GG) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…During anesthesia induction, tele-glasses also recorded laryngoscopy view, which was attached to an individual record, for both teaching and self-assessment purposes. [25,26]…”
Section: Discussion/observationsmentioning
confidence: 99%
“…During anesthesia induction, tele-glasses also recorded laryngoscopy view, which was attached to an individual record, for both teaching and self-assessment purposes. [25,26]…”
Section: Discussion/observationsmentioning
confidence: 99%
“…33 Some preliminary studies have introduced advanced technologies (e.g., Google Glass, GoPro) to help guide the novice proceduralist in endotracheal intubation. 34 Nonetheless, the anatomically challenging airway may manifest as a "Can't intubate, can't oxygenate" scenario, described as the inability to secure an ETT and failure to maintain oxygenation via a bag-valve mask (BVM) or supraglottic device. Providers should use the scalpel-bougie cricothyroidotomy approach in this scenario, given its streamlined equipment and procedure sequence (i.e., number 10 scalpel, finger, bougie, size 6.0 mm ETT).…”
Section: Airway Techniquesmentioning
confidence: 99%
“…These issues can be solved with a point-of-view camera system. A recent case series found that point-of-view cameras, the GoPro (GoPro, Inc, San Mateo, CA), and Google Glass ™ (Google, Mountain View, California), were useful in teaching endotracheal intubation [ 3 ]. The value of a point-of-view camera in teaching intubation was previously recognised more than two decades ago with the commercial release of the Airway Cam ™ (Airway Cam Technologies, Wayne, PA, USA), a head-mounted camera system worn next to the proceduralist’s dominant eye [ 4 ].…”
Section: Introductionmentioning
confidence: 99%